Modeling for Public Sphere Optimization at Local Commercial Radio Program to Enhance Public’s Accessibility and Participation for Public Services in Indonesia - Muhtar Wahyudi; Surokim As (Communication Sphere, 2015)
ABSTRACTRadio as a broadcasting media has a strategic role in promoting improved quality ofpublic services. Through its interactive broadcasting program, radio media can build publicsphere where people can express and deliver their aspirations, interests, and needs. Byoptimizing the sphere, radio can be an interactive media mediating public discuss from theaspirations, needs and interests of citizens regarding quality of various types of public servicesorganized either by governmental or private. Interactive broadcasts between community andpublic service providers are mediated by professional gatekeeper provided by management ofradio. Interactive program between citizens and providers can take place in a rational, objective,accountable, equitable, free of domination, and solution. To build the system, particularly inshaping healthy media sphere for interactive dialogue process, the radio management shouldprepare the infrastructure and superstructure, especially information systems, technology, andhuman resources regarding support the quality of broadcasting program. The system is makingin professional and has to give attention to public importance and public need based onexciting, innovative, educate, and entertaint.Keywords: Commercial Media, Radio Broadcasting, Public Sphere, Interactive Program, ThePublic Service